Streptococcus Mutans Adhesion to Titanium After Brushing with Fluoride and Fluoride-Free Toothpaste Simulating 10 Years of Use - Fais, Laiza M. G. [UNESP]; Carmello, Juliana C. [UNESP]; Spolidorio, Denise M. P. [UNESP]; Adabo, Gelson Luis [UNESP] (Quintessence Publishing Co Inc, 2013)
Purpose: To assess the influence of fluoride on the adhesion of Streptococcus mutans to titanium using an experimental paradigm simulating 10 years of brushing. Materials and Methods: Commercially pure titanium (cpTi) and titanium alloy (Ti-6Al-4V) disks (6 mm in diameter and 4 mm thick) were mirror-polished and randomly assigned to one of the following six groups (n = 6): immersion (I) or brushing (B) in deionized water (groups IW [control] and BW), fluoride-free toothpaste (groups IT and BT), or fluoridated toothpaste (groups IFT and BFT). Specimens subjected to immersion were statically submerged into the solutions without brushing. For the brushed specimens, a linear brushing machine with a soft-bristled toothbrush was used. The experiments lasted a total of 244 hours. Before and after treatment, the specimens were analyzed under an atomic force microscope to determine the mean roughness (Ra) and the mean of the maximum peak-to-valley heights of the profile (Rtm). The disks were contaminated with standard strains of S mutans in well plates with brain-heart infusion broth. Adhesion was analyzed based on the numbers of colony-forming units (CFU/mL) of adhered viable cells using scanning electronic microscopy. Differences in CFU/mL between the groups were analyzed by one-way analysis of variance. Results: Immersion did not affect either surface. As suggested by Ra and Rtm, BW, BT, and BFT induced changes on the surface of cpTi, whereas only BT and BTF induced changes on the surface of Ti-6Al-4V. No significant differences were observed regarding CFU/mL among the cpTi or Ti-6Al-4V groups. S mutans adhesion was similar for all surfaces. Conclusions: The changes in titanium induced by 10 years of simulated brushing with fluoride toothpaste did not increase the adhesion of S mutans.
Keywords: cell adhesion; sodium fluoride; Streptococcus mutans; surface properties; titanium toothbrushing